Peningkatan Literasi Matematis Siswa SMKN 7 Bandar Lampung dengan Menerapkan Outdoor Learning dengan Media Klinometer - Syawardhan, Elnando; Noer, Sri Hastuti (Universitas PGRI Madiun, 2022)
Activities are complex, have a broad meaning and have many variables that influence it, namely education. Therefore, education is an essential for humans being. In addition, according to Bukunola and Widyawati stated that education is one way to introduce humans to have better knowledge and attitudes. This research is Quasy Experimental Design, which is a type of experiment that has control group, but could not work fully for controlling an external variable that affect an implementation of experiments. Outdoor Learning that has been implemented consisted of three stages, they are preparation ,implementation then follow-up stages. In the preparation stage, the teacher and students determine the object to be observed, the tools and materials used, a place of observation that is not too far from the class so that it can be reached quickly, safely for students, and an explanation of the LAS (Student Activity Sheet) as a guide in observations. From all discussion above, that could be opened in general who students who accept an application of outdoor learning appear to increase their mathematical literacy. This can be seen in the ability to solve problems that are still accustomed to procedural explanations and are not real in the form of real observations in the classroom and outdoor learning.